Pengaruh Makroekonomi Terhadap Pergerakan Indeks Harga Saham Pada Indeks Saham Syariah Indonesia (ISSI) Di Bursa Efek Indonesia (BEI) Periode Mei 2015 - Mei 2021 - Qodir Muan (JASIE, 2022)
The capital market is a financial instrument or securities that describes one of the national economic developments. The capital market is a means of funding for companies and other institutions (government), and as a means for investing activities. Thus, the capital market facilitates various facilities and infrastructure for buying and selling activities and other related activities. One of the factors that can affect stock prices in the capital market is macroeconomics. This study aims to test and determine whether macro variables such as Exchange Rates, Interest Rates, Inflation and World Oil Prices affect the Stock Price Index on the Indonesian Sharia Stock Index (ISSI). This research is a quantitative with time series data from May 2015 to May 2021. The data used is secondary data and analyzed using multiple linear analysis. The results of the analysis show that the variables of Exchange Rate, Interest Rate, Inflation and World Oil Prices have a significant effect on the stock price index on the Indonesian Sharia Stock Index (ISSI) and partially show that only inflation has no effect on the stock price index on the Stock Price Index. Indonesian Sharia Stocks (ISSI) while the Exchange Rate, Interest Rate, and World Oil Price variables partially have effect on the stock price index on the Indonesian Sharia Stock Index (ISSI).Keywords : Exchange Rates, Interest Rates, Inflation, World Oil Prices, Indonesian Sharia Stock Index (ISSI)